Determinants of quality pledge among five-star hoteliers: a PLS-SEM approach - Ma’amor, Hairunnisa; Hashim, Nurhazirah; Achim, Nur'Ain; Muhamad Yunus, Nor Sara Nadia; Haque, A. K. M. Ahasanul (2017)
Abstract:Employee commitment to service quality so-called 'Quality Pledge' initially encompasses an employee's loyalty and their willingness to put an extra effort in their work by following the organizational values which lead them to remain in the organization. Nevertheless, in order to measure the quality pledge in five-star hotel industry, more investigation on the hoteliers ' ethical climate is required. Besides, hoteliers will look for and choose to work in the hotel that matches their ethical preferences. Therefore, the aim of this study is to determine the determinants of hotelier's ethical climate towards quality pledge. Convenient sampling was used, and 167 five-star hoteliers participated. Based on the findings, the results show that only benevolence and principled climates were the determinants of the hotelier's quality pledge. This study recommends that the hotel should maintain and cultivate suitable ethical climates based on employees commitment to service quality, thus enhance their commitment to provide excellent quality service. It is hoped that this research will contribute to the body of knowledge and shed some light on the possibility of achieving the national aims of becoming a high-income economy by 2050.